Ex vivo-expanded autologous adipose tissue-derived stromal cells ensure enhanced fat graft retention in breast augmentation: A randomized controlled clinical trial. (8th July 2020) - Kølle, Stig-Frederik T.; Duscher, Dominik; Taudorf, Mikkel; Fischer-Nielsen, Anne; Svalgaard, Jesper D.; Munthe-Fog, Lea; Jønsson, Bo; Selvig, Peter B.; Mamsen, Frederik P.; Katz, Adam J.
Abstract: Autologous fat grafting and implant surgery are used for volume restoration in plastic surgery. With the aim of producing a treatment superior to current solutions, we report a randomized, controlled, data assessor-blinded clinical trial comparing fat grafts enriched with ex vivo-expanded autologous adipose-derived stromal cells (ASCs) to nonenriched fat grafts in breast augmentation. The intervention group received ASC-enriched fat grafts (≥20 × 10 6 viable ex vivo-expanded ASCs per milliliter fat), and the control group received conventional nonenriched fat grafts. Volume retention was measured by magnetic resonance imaging, and clinical photographs were taken simultaneously for outcome evaluation. ASC-enriched fat grafts had significantly higher retention rates (mean = 80.2%) compared with conventional fat grafts (mean = 45.1%). Clinical photos showed statistically significant superior results in the intervention group, assessed by independent clinical experts. These results improve the prospects for using culture-expanded ASCs in both reconstructive and cosmetic volume restoration and make the procedure an attractive alternative to conventional fat grafting and implants. This study is registered at www.ClinicalTrials.gov, number H-16046960. : Abstract : Ex vivo-expanded adipose tissue-derived stromal cells ensure enhanced fat graft retention and superior clinical outcomes in breast augmentation. With a high survival of the injected volume, no second augmentation procedure was needed. The results improve the prospects for using expanded ASCs in reconstructive and cosmetic volume restoration and make the procedure an attractive alternative to conventional fat grafting and implants.